MRNA decapping: finding the right structures. (5th November 2018) - Charenton, Clément; Graille, Marc
Abstract : In eukaryotes, the elimination of the m 7 GpppN mRNA cap, a process known as decapping, is a critical, largely irreversible and highly regulated step of mRNA decay that withdraws the targeted mRNAs from the pool of translatable templates. The decapping reaction is catalysed by a multi-protein complex formed by the Dcp2 catalytic subunit and its Dcp1 cofactor, a holoenzyme that is poorly active on its own and needs several accessory proteins (Lsm1–7 complex, Pat1, Edc1–2, Edc3 and/or EDC4) to be fully efficient. Here, we discuss the several crystal structures of Dcp2 domains bound to various partners (proteins or small molecules) determined in the last couple of years that have considerably improved our current understanding of how Dcp2, assisted by its various activators, is recruited to its mRNA targets and adopts its active conformation upon substrate recognition. We also describe how, over the years, elegant integrative structural biology approaches combined to biochemistry and genetics led to the identification of the correct structure of the active Dcp1–Dcp2 holoenzyme among the many available conformations trapped by X-ray crystallography. This article is part of the theme issue '5′ and 3′ modifications controlling RNA degradation'.